Renal Function and its Time‐Sensitive Influence on Survival Rates of Acute Myocardial Infarction - Hirota Kida; Yuki Matsuoka; Daisuke Sakamoto; Shungo Hikoso; Daisaku Nakatani; Katsuki Okada; Akihiro Sunaga; Taiki Sato; Tetsuhisa Kitamura; Yasuhiko Sakata; Hiroshi Sato; Masatsugu Hori; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Primary percutaneous coronary intervention is the preferred treatment for acute myocardial infarction. However, in patients with chronic kidney disease (CKD), the use of contrast media can exacerbate renal dysfunction, often necessitating alternative strategies. The impact of CKD on acute myocardial infarction prognosis, particularly in the context of percutaneous coronary intervention, is not fully understood. Methods and Results This study utilized real‐world registry data from the OACIS (Osaka Acute Coronary Insufficiency Study) to evaluate prognosis across different CKD grades, including advanced CKD and hemodialysis. From a database of 12 093 patients with acute myocardial infarction, we identified 8411 patients with renal function data at admission (a median follow‐up period of 1765 days). These patients were classified into 8 CKD categories based on estimated glomerular filtration rate (eGFR); G1 (eGFR≥90 mL/min per 1.73 m2): n=1122, G2 (90>eGFR ≥60 mL/min per 1.73 m2): n=3588, G3a (60>eGFR≥45 mL/min per 1.73 m2): n=1923, G3b (45>eGFR≥30 mL/min per 1.73 m2): n=1030, G4: (30>eGFR≥15 mL/min per 1.73 m2): n=473, G5a: (15>eGFR≥8 mL/min per 1.73m2): n=80, G5b: (eGFR<8 mL/min per 1.73 m2): n=53 and hemodialysis: n=142. Percutaneous coronary intervention rates declined with advancing CKD, reaching the lowest in G5a (80.3%) but increasing again in G5b and hemodialysis groups (≈90%). Thirty‐day all‐cause mortality rates increased with CKD severity, with a notable reduction in G5b (9.4%) before rising again in patients with hemodialysis (16.9%). Long‐term data showed a progressive worsening of prognosis with advanced CKD, culminating in the poorest outcomes among patients with hemodialysis. Conclusions This study demonstrated differential impacts of CKD severity on short‐ and long‐term clinical outcomes in the context of patients with acute myocardial infarction.